(untitled) (International Seven Journal of Multidisciplinary, 2023)
Although there are countless illustrated books, children with special needs in children’s books and stories appear only as extras or supporting characters, with the main character being molded to generic social standards. This article reports on the experience of creating a literary project of my own, addressing the theme of the protagonism of individuals with special needs in children’s literature. To help organize and complete the stages, a design method was used, which has an open structure with the possibility of including or removing certain stages, shaping itself according to the project’s evolving guidelines via exploration of the creative process. The books feature stories of children who become superheroes and overcome their limitations using their superpowers related to their medical condition. Through literature and its illustrations, we reach children’s imaginations in order to convey ideas, establish social and cultural moments and rethink concepts. It is hoped that the initiative to create this literary content will promote recognition of the unique abilities of children with disabilities and that they will feel more understood and appreciated when reading books that portray characters like them.